How I started home schooling: founding stories of mothers who home school their children. Issue 2 (4th March 2019) - Neuman, Ari; Guterman, Oz
Abstract: Home schooling has become increasingly widespread in recent decades. Much research has been conducted regarding different aspects of the practice, including parents' reasons for choosing home schooling. These are often quantitative studies that directly examine these reasons and frequently cite rational reasons. In contrast, the present research is a qualitative study that examined stories in order to understand the initial reasons underlying the decision of parents to educate their children at home. An analysis of interviews with 25 mothers who home school their children yielded numerous reasons for home schooling, including some that have not been cited in the research literature. Unlike previous studies, the present examination indicated two categories: rational, deliberate change and arbitrary change. The use of open research tools that indirectly inquire about the reasons for choosing home schooling enabled the identification of a second category, arbitrary change. The implications of these results for researchers of home schooling, home-schooling families and policy-makers are discussed.